Relationship Between D-Dimer Levels and Neutrophil Lymphocyte Ratio and Platelet Lymphocyte Ratio in Deep Vein Thrombosis Patients - Lubis, Maisyarah Farhati; Heny Syahrini Lubis; Gatot , Dairion (Journal of Society Medicine, 2025)
Introduction: Venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), is associated with activation of coagulation and inflammation. In DVT, the coagulation process is often accelerated by inflammatory mediators, causing fibrinolytic disruption and increasing D-dimer levels. D-dimer testing, with its high negative predictive value, is commonly used as a screening tool for thromboembolic events. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are inflammatory markers that can be easily calculated from routine blood tests and may assist in the early detection of DVT. This study aims to evaluate the relationship between D-dimer levels and both NLR and PLR in DVT patients at Adam Malik Hospital. Method: This analytical observational study used a cross-sectional design. Secondary data were collected from medical records of DVT patients treated at Adam Malik Hospital between June 2022 and June 2024. NLR and PLR were the independent variables, while D-dimer level was the dependent variable. Data were analyzed using Spearman’s rho correlation test. Results: Among 100 patients, 38% were aged over 59 years, with equal gender distribution. The most common comorbidity was infection (71%), and 62% had hospital stays longer than 7 days. A significant positive correlation was found between D-dimer levels and NLR (p = 0.001, r = +0.350). However, there was no significant correlation between D-dimer levels and PLR (p = 0.610, r = –0.052). Conclusion: There is a significant association between D-dimer levels and NLR, but no significant relationship between D-dimer levels and PLR in DVT patients.